2008
DOI: 10.1038/modpathol.3800976
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic markers for gastrointestinal stromal tumors in Norway

Abstract: Gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor in the gastrointestinal tract. The diagnosis of GIST is based on histology together with a panel of immunohistochemical markers; the most important is KIT (CD117). A total of 434 cases of GISTs were confirmed by histology and immunohistochemistry, and incorporated into tissue microarrays. Validation of histological features as well as the prognostic value of two immunohistochemical biomarkers (p16 and L1) was assessed. High mitotic rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 33 publications
(35 reference statements)
0
51
1
1
Order By: Relevance
“…In the same study, concurrent overexpression of p73 and p16 Ink4a was significantly correlated with the p16 Ink4a overexpression in cancer C Romagosa et al lymph node metastasis, positive immunohistochemistry for p53, vascular invasion and negative progesterone receptors. Also, in some non-epithelial lesions, such as high-grade astrocytoma or gastrointestinal stromal tumors, overexpression of p16 Ink4a correlates with a poor prognosis and seems to be an unfavorable prognostic indicator (Arifin et al, 2006;Steigen et al, 2008).…”
Section: Subcellular Location Of P16 Ink4a Overexpressionmentioning
confidence: 99%
“…In the same study, concurrent overexpression of p73 and p16 Ink4a was significantly correlated with the p16 Ink4a overexpression in cancer C Romagosa et al lymph node metastasis, positive immunohistochemistry for p53, vascular invasion and negative progesterone receptors. Also, in some non-epithelial lesions, such as high-grade astrocytoma or gastrointestinal stromal tumors, overexpression of p16 Ink4a correlates with a poor prognosis and seems to be an unfavorable prognostic indicator (Arifin et al, 2006;Steigen et al, 2008).…”
Section: Subcellular Location Of P16 Ink4a Overexpressionmentioning
confidence: 99%
“…14 종양이 완전 절제된 경우 5년 생존율 은 48∼65% 정도이나 천공이 된 경우 24%까지 떨어지며 이는 복강 내 파종 때문일 것으로 추정된다. 15 자발적으로 또는 수술 시에 종괴가 파열될 경우 예후가 좋지 않다. 16 감염과 관련된 임상소견에서 복강 내 농양이 동반된 큰 종괴 가 있을 때 드물지만 GIST와 관련성을 고려할 필요가 있다.…”
Section: 서 론unclassified
“…Once recurrence has occurred median survival is 9-16 months. 7,12,16 Ulusan S et al reported a case of ruptured GIST with pelvic abscess in a 52 years old woman. 18 To our knowledge, our case is the second published report of a spontaneously ruptured GIST of the small bowel presented with abscess cavities.…”
mentioning
confidence: 99%
“…2 Perforation of the tumor lowers the five-year survival to 24%, probably due to peritoneal dissemination. 12 Local and regional lymph node involvement is infrequent in GIST. 14,15 GIST's presenting with perforation, attention needs to be paid, in view of possible recurrence of the tumor.…”
mentioning
confidence: 99%
See 1 more Smart Citation